The influence of quadriceps and hamstring strength on balance performance - Sercan Yılmaz; İbrahim Erdemir (Physical Education of Students, 2023)
Background and Study Aim. Muscular strength and balance are important components of athletic performance, and the muscles around the knee (Quadriceps and Hamstrings) provide joint stability when the knee is in motion. The aim of this study was to analyze the correlation between quadriceps/hamstring (H/Q) muscle strength, Hamstring/Quadriceps (H/Q) strength ratio and balance performance.